Experimental Study on Cavity Formation and Ground Subsidence Behavior Based on Ground Conditions - Sungyeol Lee; Jaemo Kang; Jinyoung Kim; Myeongsik Kong; Wonjin Baek (Applied Sciences, 2025)
Ground subsidence is a significant geotechnical hazard in urban areas, leading to property damage, casualties, and broader societal issues. This study investigates the mechanisms of cavity formation and ground subsidence through laboratory model tests using Korean standard sand and marine clay under controlled conditions. A transparent soil box apparatus was fabricated to simulate sewer pipe damage, with model grounds prepared at various relative densities, groundwater levels, and fines contents. The progression of cavity formation and surface collapse was observed and quantitatively analyzed by measuring the time to cavity formation and ground subsidence, as well as the mass of discharged soil. Results indicate that lower relative density accelerates ground subsidence, whereas higher density increases cavity volume due to greater frictional resistance. Notably, as the fines content increased, a tendency was observed for ground subsidence to be increasingly suppressed, suggesting that cohesive clay particles can limit soil loss under seepage conditions. These findings provide valuable insights for selecting backfill materials and managing subsurface conditions to mitigate ground subsidence risks in urban infrastructure.